The Effectiveness of the Early Start Denver Model on Empathy and Adaptive Behavior in Preschool Children with Autism Spectrum Disorder - Maruf Al-Sadi , Rawaa Izzat; Sajjadian , Ilnaz; Al-Araji , Ibrahim Mortadha; Golparvar, Mohsen (Iranian Journal of Neurodevelopmental Disorders, 2024)
Objective: This study aimed to determine the effectiveness of the Early Start Denver Model (ESDM) on empathy and adaptive behavior in preschool children with ASD.Methods and Materials: This quasi-experimental study employed a pretest-posttest design with follow-up and a control group. The statistical population included all preschool children aged 3 to 5 years attending the Autism Center at Baghdad Health Complex in 2024. A total of 30 children diagnosed with ASD were selected using purposive sampling based on inclusion and exclusion criteria. They were randomly assigned to experimental and control groups (15 children in each group). The experimental group received 10 sessions of ESDM, each lasting 60 minutes, while the control group was placed on a waitlist without any intervention. Data collection instruments included the Bahr Empathy Questionnaire and the Vineland Adaptive Behavior Scales. Data were analyzed using repeated-measures ANOVA with SPSS version 23.Findings: The results revealed significant differences in the mean scores for empathy and adaptive behavior between the pretest and posttest stages, as well as between the pretest and follow-up and the posttest and follow-up stages in the intervention group (p < .001). Empathy and adaptive behavior showed improvements in the posttest and follow-up stages compared to the pretest. Furthermore, scores remained stable in the follow-up stage compared to the posttest.Conclusion: The findings suggest that the ESDM can enhance empathy and adaptive behavior in preschool children with ASD by improving their social skills. This intervention empowers children to address behavioral challenges and serves as a foundation for future research on preschool interventions for children with ASD. It is recommended that healthcare and counseling centers adopt the ESDM to address behavioral challenges in these children.